Acting in musical theatre : a comprehensive guide - Deer, Joe; Dal Vera, Rocco (London: Routledge, 2021)
"Acting in Musical Theatre remains the only complete course in approaching a role in a musical. It covers fundamental skills for novice actors, practical insights for professionals, and even tips to help veteran musical performers refine their craft. Updates in this expanded and revised third edition include: A "Resource Guide" that includes Teaching Materials and Syllabi for long and short-courses. Updated examples, illustrations and exercises from more recent musical styles and productions such as Hamilton, and Dear Evan Hansen. Revision of rehearsal and performance guidelines to help teachers with less-experienced students avoid common problems. Updated and expanded further reading lists for specific subject areas, to guide readers through their own studies. New notes in the "The Profession" chapters to reflect the latest trends in casting, self-promotion and audition practice. A comprehensive revision of the book's companion website, including syllabi for a range of short and long-form courses, Power Point slide decks and printable handouts for every chapter. Acting in Musical Theatre's chapters divide into easy-to-reference units, each containing group and solo exercises, making it the definitive textbook for students and practitioners alike"--
Includes bibliographical references and index.
Keywords: Acting in musical theater; Musical theater